Cobalt-doped biochar derived from coir fiber activation for peroxymonosulfate degradation of methylene blue - Le Minh Tri; Nguyen Thanh Tung; Ngo Van Thanh Huy; Tran Anh Khoa; Tran Anh Khoi (Journal of Military Science and Technology, 2025)
In this work, metal-impregnated biochar (Co-Biochar) was used to activate peroxymonosulfate (PMS) and degrade methylene blue (MB) in aqueous solutions. This procedure illustrates a possible method for transforming garbage into useful commodities. Coconut fiber was pyrolyzed in an inert environment to produce biochar, which was then modified with metal salts using the co-precipitation technique. The structural features of the resultant material were studied using sophisticated analytical methods such as scanning electron microscopy (SEM), energy-dispersive X-ray spectroscopy (EDS), and nitrogen adsorption-desorption isotherms. Following PMS activation, the catalyst degraded MB with remarkable efficiency. More than 90% of the MB was removed within 15 minutes using optimum conditions (0.05 g of catalyst, 100 mL of 50 mg/L MB solution, and 400 mg/L PMS). Additionally, the effects of various reaction parameters, such as catalyst dosage, PMS concentration, solution pH, and reaction temperature, were investigated. The findings suggest that Co-Biochar holds significant potential as a PMS activator for the treatment of MB in textile wastewater.